Insect Diversity in the Pine Forest Area of Mount Nona, Ambon City - Armando C Batuwael; Fransina Latumahina; Cornelia M Wattimena (Tropical Small Island Agriculture Management, 2025)
This study aims to determine the diversity of insects in the protected forest area of Kota Nona Ambon, as well as the diversity, abundance, and distribution of insects in the area, in order to detect the quality of forest health early. In general, this study employed a sample extraction method. An observation path was created using an inventory method to collect insect data, with a width of 20 meters and a span of 100 meters, and a distance of 10 meters between paths. Data collection on attacks was then carried out. Insects were collected directly, and pitfall traps were set at a distance of 10 meters. Another type of trap was then installed at the next 10 meters along the path. Plots measuring 20 m x 20 m were created on each insect observation path. There are 13 types of insects found in the Gunung Nona forest area, with a total of 185 individuals in 8 orders, namely Diptera, Lepidoptera, Coleoptera, Aranae, Odonata, Spiroboliida, Hymenoptera, which are spread across 10 families, namely: Callipholidae, Nymphlidae, Pieridae, Muscidae, Culicidae, Araneidae, Alydidae, Libellulidae, Scarabaeidae, Erebidae, Fomicidae.